Punishment and Proportionality:: The Estoppel Approach - Kinsella, Norman Stephan (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
From the perception that the theory of punishment is underdeveloped in the libertarian thought, the author develops an approach to explain how punishment could be justified. For that purpose, defends a general theory of punishment which is retributivist/retaliatory, consistent with the libertarian principles.